Os desvios de um Dândi : erotismo em duas séries artísticas de Wesley Duke Lee - Borges, Lívia Santolin (2016)
This research presents a dialogue between eroticism and art through two series of artwork Wesley Duke Lee. In the light of different authors, investigates the eroticism definition and Eros symbology in different peoples and cultures. Establishes connectin